Art Spiegelman's 'Little Signs of Passion' and the emergence of hard-core pornographic feature film. Issue 8 (2nd August 2020) - Williams, Paul
ABSTRACT: Art Spiegelman's underground comic 'Little Signs of Passion' (1974) juxtaposes romance comics against hard-core pornographic feature films. In the early 1970s pornography was defended as an expression of moral and artistic freedom but this comic shows that hardcore's narrative conventions were as standardised and commercially driven as anything in the romance comics. Spiegelman's text reveals that, despite the diversification of porn film audiences in the early 1970s, the viewing pleasures these films offered remained heavily gendered. And, unlike other underground parodies of the romance comics, Spiegelman does not deride that genre's conventions but admires their enduring power.